HS628 : A potential genetic stock for resistance to new virulent pathotypes of black, brown and yellow rusts of wheat (Triticum aestivum L.) - Pal, Dharam; Bhardwaj, SC; Khan, Hanif; Patial, Madhu (Journal of Cereal Research, 2018)
Doi.org/10.25174/2249-4065/2018/76849